Validating The Impact of Psychological, Physical, and Social Factors On Workplace Well-Being at Construction Sites - Radzi, Afiqah R.; Rahman, Rahimi A.; Alias, Ahmad Rizal; Almutairi, Saud (International Journal of Integrated Engineering, 2023)
A good workplace well-being environment can increase employee resilience, work engagement, project performance, and productivity, as well as reduce sick days. Research suggests that physical, psychological, and social factors are the underlying factors for a good workplace well-being However, the underlying factors for workplace well-being at construction sites may differ. This study aims to validate the relationships between underlying factors (i.e., physical, psychological, and social) and workplace well-being at construction sites. A questionnaire survey was developed from a list of factors influencing workplace well-being and distributed to construction professionals. The collected data was analyzed using confirmatory factor analysis (CFA) to validate the relationships between the underlying factors and workplace well-being at construction sites. The analysis revealed that physical, psychological, and social factors are also influencing workplace well-being at construction sites. Researchers and industry practitioners can use these findings to confidently establish strategies to increase workplace well-being of construction workers.